PENGARUH MEDIA APLIKASI TIKTOK TERHADAP SIKAP KERJASAMA SISWA DALAM PEMBELAJARAN AKTIVITAS RITMIK - Septian Rijalul Hakiki; Rhama Nurwansyah Sumarno; Aria Kusuma Yuda Ryanto; Irfan Zinat Achmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the extent to which the use of TikTok application media influences the improvement of students' cooperative attitudes in rhythmic activity material in physical education subjects. The study was conducted at MAN 2 Tangerang with a quantitative approach using a pre-experimental experimental method and a one group pretest-posttest design. The research sample consisted of 35 students of grade XI-4, selected from a total population of 260 students. Data collection was carried out through an initial test (pretest) and a final test (posttest) with an instrument in the form of a cooperation attitude questionnaire. The results of the analysis showed that the use of TikTok media had a positive and significant effect on improving students' cooperative attitudes in the rhythmic activity learning process. Based on statistical tests, there was an increase in cooperative attitudes in the class that received treatment. Therefore, TikTok application media can be considered an effective tool in supporting rhythmic activity learning, especially in improving students' cooperative attitudes.